ANALISIS KINERJA KEUANGAN LEMBAGA AMIL ZAKAT DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) (Studi pada Lembaga Amil Zakat Dompet Dhuafa Republika) - Refia Alfina; Purnama Putra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
Zakat is one of the important sectors in Islamic philanthropy, currently the collection of zakat has developed quite rapidly. Along with the increasing performance of collecting zakat funds, the Zakat Management Organization (OPZ) is also growing rapidly. As an OPZ institution, it should be able to show good performance, one of which is the efficiency of financial performance. This study aims to measure the efficiency of the Dompet Dhuafa Republika Amil Zakat Institution (LAZ), to determine whether the LAZ under study has carried out its duties properly, and as an evaluation material to improve the performance of LAZ which is the object of research. The research method used is a descriptive method with a quantitative approach. Data collection techniques used in this study were library research and field research. The type of data used is secondary data in the form of financial reports of the Dompet Dhuafa Republika (DDR) amil zakat institution for the 2016-2017 period. The measurement of this research uses the non-parametric Data Envelopment Analysis (DEA) method with a production approach. The variables used in this study were divided into 2 types, namely input variables and output variables. Input variables include personnel costs, operational costs, and total assets. While the output variables include: collected funds, distributed funds, and total mustahik. The data were processed using the Banxia Frontier Analyst 4.3 computer program. Based on the research that has been done, the results of the 2016 LAZ DDR efficiency level were 100%, while in 2017 it was 98.13%. Inefficiency occurred in 2017 due to variables that did not reach the target, including: personnel costs, operational costs, total assets, funds raised and funds channeled. In general, it can be concluded that the performance of LAZ DDR in 2016 is better than 2017. The results of this study will be able to help LAZ DDR improve the level of efficiency in the next period in order to obtain good performance.